Language and society - Mantero, Miguel; Watzke, John L.; Miller, Paul Chamness; Endo, Hidehiro (Emerald Publishing Limited, 2022)
Language and Society is the fifth volume of the Readings in Language Studies series published by the International Society for Language Studies, Inc. Volume five sustains the society's mission to organize and disseminate the work of its contributing members through peer-reviewed publications. The book presents international perspectives on language and society in three thematic sections: teaching practices & pedagogy, policy, and culture. A resource for scholars and students, Language and Society represents the latest scholarship in new and emergent areas of inquiry.
Includes index.
Keywords: Sociolinguistics.; Language and languages -- Study and teaching.; Language and culture.; Education -- Language Experience Approach.; Language learning: specific skills.; Teaching skills and techniques.; elektronické knihy; electronic books